A biogeographic analysis of the species Fragaria vesca using microsatellite markers on a worldwide plant collection - Hrannar Smári Hilmarsson 1984- (2015)
The woodland strawberry, Fragaria vesca L., has the widest distribution of its genus. It can be found across North-America, all over Europe and into Asia. F. vesca has become an important research model benefitting from its small genome as well as both easy propogation and maintainance. A vast collection and research on natural variation is imperative to the advancement of research in the field of the Rosa (Rosaceae) plant family, the third most economically important of all plant families. Another importat reason for assessing the genetic population structure of the F. vesca is its vast distribution and the effect of climate change through the ages, which could shed light on the dispersal route of the species during and after the last glacial maximum. The aims of this study were to collect individuals of F. vesca representing the entire geographic distribution, assess their genetic diversity and to shed light on the origin of the Icelandic F. vesca population. In this study, a collection of 445 plants were gathered from all corners of the geographical distribution. Of those, 300 plants were analysed using 66 of the 68 microsatellite markers tested. Their mean allele number per locus was 3.94 and the mean polymorphic information content value was 0.13. Ten markers were monomorphic and 13 biallelic. The collection of plants was analysed using Beyasian clustering analysis software BAPS and STRUCTURE. The two methods resulted in contrasting number of clusters for the data. The only corresponding results were the great divergence between the American population and the European. Also it was prominent in both methods that the Icelandic population was a separate cluster in the European populations. The two genetic distance methods used showed that the Icelandic population was closest genetically to the set of cultivars used in this study. Furthermore, the results revealed no population structure in Iceland suggesting recent dispersal and refuting any suggestions of glacial survival.